ANALISIS LAPORAN KEUANGAN DENGAN MENGGUNAKANMODEL ALTMAN Z-SCORE UNTUK MEMPREDIKSI POTENSI KEBANGKRUTAN PADA PERUSAHAAN KOSMETIK PT. MUSTIKA RATU PERIODE 2015-2019 - Sarumaha, Novitriani (LPPM Universitas Nias Raya, 2024)
This is proven by the average Zi score of 2.20, which means that the Zi score is between 1.81<Z-score<2.99 so it is categorized as a company. who have financial difficulties, but the possibility of being saved and the possibility of bankruptcy are equally large depending on the policy decisions of company management as decision makers. From the results of the research, the author suggests that company management should improve the company's strategy in managing all assets owned by the company to obtain profits and adopt policies to increase the company's total income so that it provides more positive profit or profits.